PENGARUH MOTIVASI KERJA, SELF-EFFICACY, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DI PERUSAHAAN QAYLA JEWELRY - Rahmadani, Erlina Diah; Nuvriasari, Audita (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to analyze the influence of Work Motivation, Self-Efficacy, and Job Satisfaction on Organizational Commitment at Qayla Jewelry Company. The research method used is a quantitative approach. The population used in this study were 48 employees who worked at the Qayla Jewelry company. Data collection techniques through distributing questionnaires. The data analysis tool uses multiple linear regression. The results of this study indicate that: (1) Work motivation has a positive and significant effect on organizational commitment at Qayla Jewelry Company. (2) Self-Efficacy has a positive and significant effect on organizational commitment at Qayla Jewelry Company. (3) Job Satisfaction has a positive and significant effect on organizational commitment at Qayla Jewelry Company.